KARAKTERISTIK KUALITAS AIR PADA DAERAH TANGKAPAN HUJAN PARIT BANSIR - Cahyono, Andri; Nurhayati, -; Gani, Umar A (JeLAST : Jurnal PWK, Laut, Sipil, Tambang, 2018)
Bansir Ditch area is located in the middle of Pontianak City whose development area increased quite fast. Unregulated land use causes drainage problems in urban areas to become very complex, in addition to its late arrangement. This is also caused by low awareness of the function of Bansir Ditch. Observations made include tidal observation, measurement of velocity, discharge and water quality. Water quality parameters studied were physics, organic chemistry and microbiology. Land use observations based on aerial photographs of 2006, 2008, 2014 and 2017. The results obtained are (1) Type of tidal Bansir Ditch is single diurnal tide that is 1 time tide and 1 receding in 1 day. (2) The flow velocity of Bansir Ditch from upstream to downstream is relatively slow and the flow is also small. The highest velocity is 0.152 m/sec and the greatest discharge during measurement is 0.259 m3/sec. (3) Land use change influences water quality in Bansir Ditch, this is proven from the observation of water quality which results show that the Bansir Ditch is getting polluted and the aesthetics of the trenches becomes poor. The biggest factor is the household and industrial wastes from settlements that enter the ditch, such things will undermine the quality of the Bansir Ditch in the long term. Ways that can be done is control the building along the Bansir Ditch according to the riparian zone and make the rules about the use of land use, especially facing directly with the Bansir Ditch.Keywords: Bansir ditch, Tidal, Water quality